2022
DOI: 10.1021/acsaom.2c00033
|View full text |Cite
|
Sign up to set email alerts
|

Bilayer CdS Structure: A Promising Candidate for Photocatalytic and Optoelectronic Applications

Abstract: Density functional theory methodology has been adopted to investigate the structural, electronic, and optical properties of the CdS bilayer system and compare it with the CdS monolayer. For the bilayer system, five different types of stacking modes have been considered. The binding energy calculation suggests that the AA2 stacking mode is the most energetically favorable. Both the CdS monolayer and AA2 stacked CdS bilayer possess hexagonal symmetry, but the lattice constant slightly increases in the case of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 60 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…The physical phenomena and potential applications of two-dimensional (2D) stacking materials have initiated significant interest in the fields of nanoelectronics, visible-light-driven photocatalysts, energy storage, and conversion. However, studies have shown that homostructure-layered materials may limit device applications. To overcome this limitation, integration of the inherent characteristics of two or more 2D monolayers has been widely regarded as the most promising method through the construction of van der Waals heterostructures (vdW-HSs). , Stacked layers of 2D materials in vdW-HSs are blended by weak van der Waals forces. This has recently emerged as a promising platform for the development of ultrafast and low-power electronic and spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The physical phenomena and potential applications of two-dimensional (2D) stacking materials have initiated significant interest in the fields of nanoelectronics, visible-light-driven photocatalysts, energy storage, and conversion. However, studies have shown that homostructure-layered materials may limit device applications. To overcome this limitation, integration of the inherent characteristics of two or more 2D monolayers has been widely regarded as the most promising method through the construction of van der Waals heterostructures (vdW-HSs). , Stacked layers of 2D materials in vdW-HSs are blended by weak van der Waals forces. This has recently emerged as a promising platform for the development of ultrafast and low-power electronic and spintronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…To overcome this limitation, integration of the inherent characteristics of two or more 2D monolayers has been widely regarded as the most promising method through the construction of van der Waals heterostructures (vdW-HSs). 4,5 Stacked layers of 2D materials in vdW-HSs are blended by weak van der Waals forces. This has recently emerged as a promising platform for the development of ultrafast and low-power electronic and spintronic devices.…”
Section: ■ Introductionmentioning
confidence: 99%
“…This unique property allows CdS gas sensors to operate effectively at room temperature, eliminating the need for external heating. 67,68 Consequently, there is a need to explore CdS as a novel material in the gas sensor eld. Therefore, 2D CdS bilayers emerge as excellent candidates for highly sensitive gas sensors, given their potential for exceptional gas-sensing capabilities.…”
Section: Introductionmentioning
confidence: 99%